Endogenous progesterone levels and frontotemporal dementia: modulation of TDP-43 and Tau levels in vitro and treatment of the A315T TARDBP mouse model - Theresa N. T. Dang; Carol Dobson-Stone; Elias N. Glaros; Woojin S. Kim; Marianne Hallupp; Lauren Bartley; Olivier Piguet; John R. Hodges; Glenda M. Halliday; Kay L. Double; Peter R. Schofield; Peter J. Crouch; et al. (The Company of Biologists, 2013)
SUMMARY Frontotemporal dementia (FTD) is associated with motor neurone disease (FTD-MND), corticobasal syndrome (CBS) and progressive supranuclear palsy syndrome (PSPS). Together, this group of disorders constitutes a major cause of young-onset dementia. One of the three clinical variants of FTD is progressive nonfluent aphasia (PNFA), which is focused on in this study. The steroid hormone progesterone (PROG) is known to have an important role as a neurosteroid with potent neuroprotective and promyelination properties. In a case-control study of serum samples (39 FTD, 91 controls), low serum PROG was associated with FTD overall. In subgroup analysis, low PROG levels were significantly associated with FTD-MND and CBS, but not with PSPS or PNFA. PROG levels of >195 pg/ml were significantly correlated with lower disease severity (frontotemporal dementia rating scale) for individuals with CBS. In the human neuroblastoma SK-N-MC cell line, exogenous PROG (9300-93,000 pg/ml) had a significant effect on overall Tau and nuclear TDP-43 levels, reducing total Tau levels by ∼1.5-fold and increasing nuclear TDP-43 by 1.7- to 2.0-fold. Finally, elevation of plasma PROG to a mean concentration of 5870 pg/ml in an Ala315Thr (A315T) TARDBP transgenic mouse model significantly reduced the rate of loss of locomotor control in PROG-treated, compared with placebo, mice. The PROG treatment did not significantly increase survival of the mice, which might be due to the limitation of the transgenic mouse to accurately model TDP-43-mediated neurodegeneration. Together, our clinical, cellular and animal data provide strong evidence that PROG could be a valid therapy for specific related disorders of FTD.